Indoor radon concentration and its influencing factors in newly decorated houses and offices in Shenyang city - Hao-lan WU; Hang ZHAO; Meng-ge LI (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo examine indoor radon pollution and its associates in houses and offices with recent interior decoration in Shenyang city of Liaoning province and to provide evidence for developing targeted control measures against the pollution. MethodsFrom Shenyang Construction Engineering Quality Testing Center, we collected the data on indoor radon detections for 581 houses and 151 offices after recent interior decoration in 25 buildings in Shenyang city during 2017. The concentrations of radon were described and the relationship between the indoor radon and decoration conditions was analyzed statistically. Results The mean indoor radon concentration of the offices was significantly higher than that of the houses (75.822 ± 4.090 vs. 69.285 ± 7.128 Bq/m3, P < 0.05). The most important influencing factor of room-specific radon concentration is the floor number of the room located on. The major influencing factors of indoor radon concentration for houses included whether the white powder (mainly consisted of calcium carbonate, cellulose and white latex) being used for interior wall decoration and the distance from a main road; in addition to whether the white powder being used for interior wall decoration, the indoor radon concentration of an office also influenced by the utilization of floor, marble tile, and polyvinyl chloride floor covering. ConclusionDecoration-related factors need to be concerned for the prevention and control of indoor radon pollution in houses and offices.